A TOF and TDOA underground joint positioning method based on UWB - Xian CHEN (Meikuang Anquan)
The existing precise positioning system for mining personnel mainly adopts UWB positioning technology. The positioning method that only applies TOF requires joint ranging and orientation based on two positioning sub stations or antennas, which has problems such as long positioning time, high power consumption of positioning cards, and inaccurate orientation when underground personnel obstructed. In response to the above issues, a TOF and TDOA underground joint positioning method is proposed, which is mainly applied to one-dimensional positioning scenarios in coal mines and combines two-dimensional positioning scenarios. This method uses a positioning substation as the main base station, and connects several receivers through the CAN bus as the auxiliary base station. During the TOF ranging process between the positioning card and the main base station, the auxiliary base station completes wireless time synchronization with the main base station by listening to the interaction message timestamp of TOF positioning, and sends back two sets of TDOA positioning time difference information to the main base station. Combined with the distance value between the label and the main base station, the main base station completes the distance value calculation and validity judgment between the two sets of labels and the slave base station. A testing platform was built in a simulated tunnel for verification, and the results showed that this method combines the advantages of TOF and TDOA positioning methods, with fast positioning speed, low power consumption of positioning cards, and accurate orientation in occlusion situations.